2017
DOI: 10.1073/pnas.1614557114
|View full text |Cite
|
Sign up to set email alerts
|

Trk receptor signaling and sensory neuron fate are perturbed in human neuropathy caused by Gars mutations

Abstract: Charcot-Marie-Tooth disease type 2D (CMT2D) is a peripheral nerve disorder caused by dominant, toxic, gain-of-function mutations in the widely expressed, housekeeping gene, GARS. The mechanisms underlying selective nerve pathology in CMT2D remain unresolved, as does the cause of the mild-to-moderate sensory involvement that distinguishes CMT2D from the allelic disorder distal spinal muscular atrophy type V. To elucidate the mechanism responsible for the underlying afferent nerve pathology, we examined the sens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(140 citation statements)
references
References 74 publications
3
135
1
1
Order By: Relevance
“…However, the underlying molecular mechanism of these disorders has remained elusive. Many CMT-linked mutations seem to have no significant effect on the aminoacylation activity of the synthetase, and recent studies support a toxic gain of function mechanism, possibly involving the exposure of a neomorphic binding surface and resulting in aberrant protein interactions (He et al, 2015; Motley et al, 2011; Seburn et al, 2006; Sleigh et al, 2017). In contrast, other CMT-linked mutations have been reported to cause a loss of charging activity, suggesting that haploinsufficiency of the enzyme may be a possible contributing factor (Griffin et al, 2014; McLaughlin et al, 2012).…”
Section: Defects In Aminoacyl Trna Synthetase Function In Neurodegenementioning
confidence: 99%
“…However, the underlying molecular mechanism of these disorders has remained elusive. Many CMT-linked mutations seem to have no significant effect on the aminoacylation activity of the synthetase, and recent studies support a toxic gain of function mechanism, possibly involving the exposure of a neomorphic binding surface and resulting in aberrant protein interactions (He et al, 2015; Motley et al, 2011; Seburn et al, 2006; Sleigh et al, 2017). In contrast, other CMT-linked mutations have been reported to cause a loss of charging activity, suggesting that haploinsufficiency of the enzyme may be a possible contributing factor (Griffin et al, 2014; McLaughlin et al, 2012).…”
Section: Defects In Aminoacyl Trna Synthetase Function In Neurodegenementioning
confidence: 99%
“…Currently, two genetics experiments in flies and mice have demonstrated that dominant mutations in GARS cause CMT through toxic gain-of-function effects [10,18]. Several binding partner of CMT mutants have been discovered, including Nrp1 [25], Trk [26] and HDAC6 [27,28]. Here we presented that SIRT2, the acetylated tubulin deacetylase, is able to bind tightly with wildtype GARS comparing with CMT mutants, we didn't rule out the possibility that CMT mutants might gain the functions to increase deacetylation activity of SIRT2 which leading to decrease the acetylated tubulin.…”
Section: Disscussionmentioning
confidence: 99%
“…In addition to muscle weakness, this is followed by compromised reflexes and loss of sensation to vibration, touch, temperature and pin-prick (Sivakumar et al, 2005). These symptoms are well replicated in Gars-neuropathy mice, highlighting their potential for studying sensory pathomechanisms (Sleigh et al, 2017a).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, all assessed GlyRS mutants possess a similar conformational opening that excavates neomorphic surfaces usually buried within the structure of the wildtype enzyme (He et al, 2011(He et al, , 2015. Given that GlyRS is secreted from several different cell types (Park et al, 2012;Grice et al, 2015;He et al, 2015;Park et al, 2018), these uncovered protein regions can mediate aberrant deleterious interactions both inside and outside the cell (He et al, 2015;Sleigh et al, 2017a;Mo et al, 2018), likely accounting for non-cell autonomous aspects of pathology (Grice et al, 2015(Grice et al, , 2018. While some of these misinteractions are with neuronally-enriched proteins, the pathomechanisms underlying neuronal selectivity in CMT2D remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation